Розширення математичного апарату дискретно-неперервних мереж для автоматизації процедур їх синтезу - Gurskiy, Alexander; Denisenko, Andrey; Goncharenko, Alexander (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2024)
The paper deals with a model of an intelligent system related to the automatic synthesis of Petri nets and presents a certain stage of developing this model. The peculiarity of the extended mathematical apparatus is that it contains a combination of Petri net incidence matrices to represent various algorithms. This combination of matrices is part of the equations describing the logic control device of a complex system. Accordingly, the work also presents a well-known mathematical description of discrete-continuous systems with a controlled structure, which includes certain logical control devices. This mathematical description, based on means of discrete-continuous networks, is associated with the incidence matrix of the Petri net, which is formed as a result of a particular synthesis algorithm. At the same time, the formed Petri net represents the corresponding logical control algorithm that should ensure the effective functioning of the corresponding system. The final part of the work presents various structural schemes of logic-dynamic models of systems related to the automatic synthesis of Petri nets. Here, we determine the features of the advanced mathematical apparatus based on discrete-continuous networks to develop an intelligent system that forms logical control algorithms. It is also noted that such systems can be used to create certain control algorithms that ensure increased efficiency of the functioning of some objects in difficult and unpredictable conditions.